Decay and Sap Stain of Timber, their Causes and Prevention - Bakshi, B. K. (Indian Forester, 1953)
The paper lays down practical directions that should be followed to prevent decay and sap stain of timber from the time a tree is felled till the timber is converted. Fungi which cause decay and stain in timber usually remain active between June-July to September-October in India when the hot season coincides with the monsoon rains. Infection and subsequent growth of fungi into the wood is frequent and rapid during this period. During the remaining months of the year, the fungal activity is reduced to a minimum and the infection of wood is correspondingly reduced. Inside the wood, the fungi cannot grow if the wood is saturated with water or if the moisture content of the wood is brought below 20 per cent based on oven-dry weight of the wood. The food requirements of wood destroying and sap stain fungi and their effects on the wood are described. Methods of identifying decay and stain fungi in culture are described and the practical utilities of such determinations are stressed. Felling time should preferably be in winter when the fungus activity is minimum due to low humidity and temperature. The tree should be cut into smaller logs, barked and the surface brushed with a preservative within 48 hours after felling to give a temporary protection to the timbers. They should be quickly transported to timber yards where they may be stored completely submerged in water in log ponds or stored dry in storage yard. Hygienic methods of storage in the yard are described. Wood preservatives giving a temporary protection of logs are listed. The important role that fungi play in bringing about decay of wood has been recognized. The loss from decay in standing trees is mainly due to heart rot and to a less extent to sap rot while after conversiou, much timber in transit, storage and service is lowered in value by decay and stain, thus necessitating an increased annual cut for replacement. A considerable proportion of this loss is preventable. Prevention of heart rot in standing trees comes under tree pathology and is outside the scope of this article wruch is intended to give methods of recognizing causes of decay and sap stain and their effects on wood and to lay down brief and specific directions for minimizing losses from sap stain and decay from the time a tree is felled till the timber is finally put to service. It is felt that an insight into these problems will help our foresters and timber merchants to handle timbers safely without incurring serious losses.